Adults' Knowledge of Mathematical Orthography. - Kim, Seyeon; Douglas, Heather P.; LeFevre, Jo-Anne (Canadian Journal of Experimental Psychology / Revue Canadienne de Psychologie Expérimentale, 2025)
Mathematical orthography comprises knowledge of mathematical symbols and the conventions for combining those symbols. For example, in the expression x³ + 3x, the positions of the symbol "3" in each term dictate its meanings in the expression. To be successful mathematical problem solvers, people need to know these conventional orthographic patterns. In this study, mathematical orthography skills were assessed in an online format for 189 adults using a timed dichotomous symbol-decision task (e.g., are these expressions conventional? (|x| or ||x)). The symbol-decision task predicted unique variance in whole-number arithmetic, word problem solving, and algebra, controlling for verbal working memory. These results support the role of individual differences in mathematical orthography as a predictor of advanced mathematical skills. In contrast, a written language orthography task only predicted unique variance in word problem solving, where participants read texts. The role of mathematical orthography should be considered in models of mathematical cognition.